Organi na čipu in njihov potencial pri vrednotenju nanodostavnih sistemov - Kirbus, Klemen (Farmacevtski vestnik, 2024)
The advancement of pharmaceutical nanotechnology is accompanied by the need to evaluate nanodelivery systems, especially nanoparticles, on models that mimic in vivo conditions. This is enabled by organs-on-a-chip, which represent cells cultured in a three-dimensional extracellular matrix with relevant fluidics. This setup offers a more biorelevant environment than traditional two-dimensional static cell cultures due to the biomechanical forces that influence gene expression and cell phenotype. Most research in the field is focused on establishing complex disease models or in vitro drug evaluation. Moreover, their use is expanding to include the evaluation of nanodelivery systems and nanomedicines. These chips are primarily used to study nanoparticle transport across biological barriers and the efficacy of nanodelivery systems against tumors in vitro. Continued development is expected to expand the use of organs-on-a-chip from primarily research labs to broader applications within the pharmaceutical industry.
Keywords: Dostavni sistemi; drug delivery systems; in vitro characterisation; nanodelci; nanoparticles; organ na čipu; organ-on-achip; tumor na čipu; tumor-on-a-chip; vrednotenje in vitro